Popular Song Creativity in the Socio-cultural Context - Kablova, Tetiana; Teteria, Victor (Journal of History Culture and Art Research, 2020)
This article investigates the influence of modern social processes on musical culture, in particular, on vocal pop songs in the Ukrainian context. The culturological vector in the formation of popular vocal and song creativity as a mass culture in the context of the social and historical stage of human existence is emphasized, the concept of pop vocal music is considered. One of the most serious stages in the development of pop music culture in the context of social processes, the authors consider the problem of simplifying the concept of pop vocal popular art, its humiliation in comparison with academic vocal culture. At the same time, in the context of modern social and historical development, the emphasis is on the formation of a special kind of mass art-popular art, which becomes a mirror of socio-historical events that are important for a particular time. At the same time, in the context of modern social and historical development, the emphasis is on the formation of a special kind of mass art-popular art, which becomes a mirror of socio-historical events that are important for a particular time. The authors provide their statements about the presence in vocal and pop music of important psychological phenomena of thought, feeling, sensation, perception, judgment, which are essentially a symbolic composition of personal consciousness. It is determined that such symbolism is most fully and deeply revealed in the context of the genre content of pop vocal performance, which today is defined as a new academicism, i.e. deep and concretized professionalization that provides its own socio-communicative and expressive-artistic canons, forms the basis for understanding and interpreting events of modernity and socio-cognitive function.